2021
DOI: 10.7717/peerj.11454
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key microRNAs and the underlying molecular mechanism in spinal cord ischemia-reperfusion injury in rats

Abstract: Spinal cord ischemia-reperfusion injury (SCII) is a pathological process with severe complications such as paraplegia and paralysis. Aberrant miRNA expression is involved in the development of SCII. Differences in the experimenters, filtering conditions, control selection, and sequencing platform may lead to different miRNA expression results. This study systematically analyzes the available SCII miRNA expression data to explore the key differently expressed miRNAs (DEmiRNAs) and the underlying molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…Significant downregulation of miR-199a-3p after SCI constitutes this miRNA as a potential marker for SCI, as also observed by other authors [ 58 , 59 , 60 ]. Furthermore, miR-199a-3p was upregulated at week 14, which indicates the beneficial effects of ESWT.…”
Section: Discussionsupporting
confidence: 83%
“…Significant downregulation of miR-199a-3p after SCI constitutes this miRNA as a potential marker for SCI, as also observed by other authors [ 58 , 59 , 60 ]. Furthermore, miR-199a-3p was upregulated at week 14, which indicates the beneficial effects of ESWT.…”
Section: Discussionsupporting
confidence: 83%
“…After spinal cord ischemia-reperfusion injury, mir-144-3p is upregulated, with the main target gene involved in GMP-PKG and cAMP signaling pathways. 42 Our ceRNA regulatory network results indicate that TCONS_ 00125346-miR-125a-3p-SCARB1, TCONS_00128041-miR-338-3p-TPM1, and 1:163182618|163216364-miR-134-5p-LIMK1 are markedly altered in the post-SCI pathophysiological process, providing comprehensive insight toward identifying potential GV-EA therapeutic targets. In this case, additional, specific pathways and molecular mechanisms need to be further studied.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, GV-EA may effectively regulate the interaction between TLR2 and miR-144-3p, further reducing the inflammatory response. After spinal cord ischemia-reperfusion injury, mir-144-3p is upregulated, with the main target gene involved in GMP-PKG and cAMP signaling pathways [ 42 ]. Our ceRNA regulatory network results indicate that TCONS_00125346-miR-125a-3p-SCARB1, TCONS_00128041-miR-338-3p-TPM1, and 1:163182618|163216364-miR-134-5p-LIMK1 are markedly altered in the post-SCI pathophysiological process, providing comprehensive insight toward identifying potential GV-EA therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Zhao et al [ 16 ] showed that the lncRNA nuclear-enriched abundant transcript 1 (NEAT1) promotes the development of AD through the miR-124/beta-site amyloid precursor protein-cleaving enzyme axis. In addition, miR-291a-3p, which is associated with inflammation, oxidative stress, and apoptosis, may be downregulated in neural injury[ 17 , 18 ]; however, its role and mechanism of function in AD remain unclear.…”
Section: Introductionmentioning
confidence: 99%